MODERNISASI PEMBELAJARAN KITAB KUNING DI PONDOK PESANTREN - Ali Imron; Nasokah Nasokah; Akhmat Khoiri; Fatiatun Fatiatun; Nurul Mubin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2022)
This study aims to analyze the modernization of learning the book of Turats or the yellow book at the Hidayatul Mubtadi'in Islamic boarding school in Boja Kendal. The method used is in the form of data collection through observation, interviews with caregivers and students, and documents according to the research objectives. The results of the study indicate that to further socialize and at the same time facilitate the understanding of students studying the Turats book, it is necessary to reform the method, in other words, modernization of understanding and learning of the Turats book or the yellow book in Islamic boarding schools is very necessary.